Emulator for Generating Heterogeneous Interference Signals in the Korean RFID/USN Frequency Band - Lee, Sangjoon; Yoon, Hyungoo; Baik, Kyung-Jin; Jang, Byung-Jun (Journal of Electromagnetic Engineering and Science, 2018)
In this study, we suggest an emulator for generating multiple heterogeneous interference signals in the Korean radio frequency identification/ ubiquitous sensor network (RFID/USN) frequency band. The proposed emulator uses only one universal software radio peripheral to generate multiple heterogeneous interference signals more economically. Moreover, the physical and media access control parameters can be adjusted in real time using the LabVIEW program, thereby making it possible to create various time-varying interference environments easily. As an example showing the capability of the proposed emulator, multiple interference signals consisting of a frequency-hopping RFID signal and two LoRa signals with different spreading factors were generated. The generated signals were confirmed in both frequency and time domains. From the experimental results, we verified that our emulator could successfully generate multiple heterogeneous interference signals with different frequency and time domain characteristics.